What Makes Cocoa Farmers Convert Cocoa Land? Case Study: Two Cocoa Producing Districts in Southeast Sulawesi Province, Indonesia - Prihantini, Campina Illa; Jamil, Ahmad Syariful; Risna; Iksan; Masitah; Joka, Umbu; Septiadi, Dudi; Destiarni, Resti Prastika (Jurnal AGRISEP, 2024)
Southeast Sulawesi province, as one of the cocoa baskets and the center of the National Cocoa Movement (GERNAS), continues to experience a decline in cocoa production and land area. One factor is the widespread conversion of cocoa land. This phenomenon needs to be highlighted and studied further because it can affect the sustainability of the cocoa value chain in Southeast Sulawesi. This study aims to determine what factors influence cocoa farmers in converting cocoa farmland to other farms in Southeast Sulawesi Province's two leading cocoa-producing districts. The research sites were purposely selected because they are the two leading cocoa-producing districts in the province. This study used logistic regression analysis. Cocoa farmers in Kolaka district converted cocoa land to patchouli farming, while cocoa farmers in East Kolaka district converted their cocoa land to rice farming. The analysis results show that the main factors that significantly influence cocoa farmers' decision to convert cocoa land are cocoa farming experience and the price of other commodities (including the level of income farmers receive from farming other commodities). The primary policy that the government can take in maintaining cocoa land area is to provide price certainty for cocoa itself. So far, cocoa farmers have always faced price uncertainty, and cocoa's value chain and sustainability in Southeast Sulawesi Province need to be clarified.